2019
DOI: 10.3389/fnmol.2019.00026
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Cognitive Function and Altered Hippocampal Synaptic Plasticity in Mice Lacking Dermatan Sulfotransferase Chst14/D4st1

Abstract: Chondroitin sulfate (CS) and dermatan sulfate (DS) proteoglycans (PGs) are major extracellular matrix (ECM) components of the central nervous system (CNS). A large body of evidence has shown that CSPGs/DSPGs play critical roles in neuronal growth, axon guidance, and plasticity in the developing and mature CNS. It has been proposed that these PGs exert their function through specific interaction of CS/DS chains with its binding partners in a manner that depends on the sulfation patterns of CS/DS. It has been re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 66 publications
0
22
0
Order By: Relevance
“…Importantly, the sulfonation patterns of stem cell niche extracellular matrix proteoglycans can influence neurogenesis by regulating growth factor signalling; the most well-known being the regulation of fibroblast growth factor signalling by heparan sulfate proteoglycans within the V-SVZ (Mercier, 2016;Purushothaman et al, 2012;Yamada et al, 2017;Yu et al, 2017). Within the SGZ, chondroitin sulfate and dermatan sulfate also appear to play roles in regulating neurogenesis as well (Li et al, 2019;Yamada et al, 2018). It is possible that impaired sulfate availability during the critical postnatal developmental window, when the demand for sulfate is high, alters the patterning of ECM proteoglycans laid down in the neural stem cell niches.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the sulfonation patterns of stem cell niche extracellular matrix proteoglycans can influence neurogenesis by regulating growth factor signalling; the most well-known being the regulation of fibroblast growth factor signalling by heparan sulfate proteoglycans within the V-SVZ (Mercier, 2016;Purushothaman et al, 2012;Yamada et al, 2017;Yu et al, 2017). Within the SGZ, chondroitin sulfate and dermatan sulfate also appear to play roles in regulating neurogenesis as well (Li et al, 2019;Yamada et al, 2018). It is possible that impaired sulfate availability during the critical postnatal developmental window, when the demand for sulfate is high, alters the patterning of ECM proteoglycans laid down in the neural stem cell niches.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Kijima et al studied surface marks from patient derived xenografts and cell lines based on array comparative genomic hybridization to investigate the early stages of GBM tumorigenesis ( 48 ). In additional to research that found raised levels of systemic inflammatory markers to be correlated with cardiovascular disease ( 49 ), a recent study revealed that the specific sulfation level of DS is crucial in synaptic plasticity and is related to changes in the expression of glutamate receptors and other associated synaptic proteins ( 50 ). As such, endocan became a valuable target for GBM diagnosis and therapy.…”
Section: Roles Of Proteoglycans In Brain Cancermentioning
confidence: 99%
“…Pathophysiological mechanisms and therapies are not yet established for the disease. Several reports show that Chst14 gene deletion induces changes in the spinal cord and nervous system functions [ 1 , 8 , 13 ] as well as an abnormality of blood capillaries in the placenta [ 18 ] of mice. However, a model animal that focuses on the skin and bone (tissues related to serious symptoms of mcEDS- CHST14 ) has not been reported.…”
Section: Discussionmentioning
confidence: 99%